Pengaruh Nilai Tukar Dan Gross Domestic Bruto Terhadap Ekspor Minyak Bumi Indonesia - Wibisono, Avival Wahyu; Nuraini, Ida (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2022)
In Indonesia, one of the sectors that dominates in terms of exports is from the mining subsector where the dominant commodity is from petroleum commodities. Although oil exports in Indonesia have fluctuated, they have also become an influential contributor to exports for Indonesia. the exchange rate is the amount of a country's currency by looking at the price of an item compared to other countries, if a country's currency rises it will increase imports because the price of foreign goods is relatively cheaper than the price of goods in the country. While other variables that affect exports are Gross Domestic Product is a factor that influences to see and determine the development of the export rate. Where if a country's Gross Domestic Product increases it will affect people's purchasing power to import. The variable influencing export from the demand side is Gross Domestic Product, where if a country's Gross Domestic Product increases so that the purchasing power of a country's people will increase the value of imports. The data used are secondary data from the World Bank, the Central Statistics Agency (BPS), and Bank Indonesia (BI) and the analysis method used is panel data analysis using Fixed. Effect Model.